COMPARATIVE STUDY OF THE RELATIONSHIP BETWEEN FALL HISTORY AND THE SOCIODEMOGRAPHIC PROFILE OF OLDER ADULTS (CIPEEX, 2025)
Population aging is an irreversible, multifactorial phenomenon of great magnitude, resulting from socioeconomic factors, medical and scientific advances, and changes in reproduction and longevity patterns. This situation of age transition, related to the intrinsic complications of the aging process, highlights falls as a major in public health concern, especially in the Brazilian context, where the older adults represent 15.8% of the population. This is because falls are one of the leading causes of morbidity and mortality among the elderly, which underscores the need for further investigation. This is a cross-sectional, descriptive field study conducted with older adults enrolled at UniAPI, using a questionnaire that assesses socioeconomic aspects and the frequency of falls. In the sample of 120 people, the following characteristics can be observed: female (91.7%), “pardo” (42.5%), widowed (47.5%), incomplete elementary education (38.4%), retired (90%), and family composition with two members (42.5%). In addition, there was a 40% rate of falls in recent years, with a predominance of single episodes (47.9%), consistent with the overall sample profile. Therefore, based on this study, it is possible to observe a sociodemographic profile of Brazilian older adults in the context of demographic transition, elucidating the high incidence of falls among this population.
Keywords: Elderly; Accidents due to falls; Demography